Other experiences of planning for reconstruction and transformation: A narrative of planning and development histories in Hammanskraal-Temba - van Huyssteen, Elsona (Acta Structilia, 2001)
Hammanskraal-Temba is one of the areas in South Africa that experiences a multitude of problems, ranging from an informal settlement lacking services, a struggling local economy, unemployment and housing shortages, to land claims and border disputes. However, a study of the historical development of the area and the impact of development initiatives such as planning policies and legislation on the area indicated the wide range of experiences and interpretations of the role of planners and planning. In an attempt to highlight these interpretations and the various [hi]stories, an alternative approach towards local historic analysis is used and is illustrated by some extracts from the Hammanskraal-Temba case study. The article aims in particular to illustrate some other experiences of planning for reconstruction and transformation and their implications for planning and planners. The article is based on a paper delivered at the Planning History Study Group: Millennium Conference in May 2000, at the Howard College at the University of Natal in Durban. The conference focused on the role of planning and planners in reconstruction.